The role of oral Curcumin Nanomicell on improvement of menstrual disorders, depression and anxiety in women with Polycystic Ovarian Syndrome - Fatemeh Zare Bidaki; Shahla Chaichian; Sepideh Arbabi Bidgoli (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2021)
Introduction: Regarding the increasing prevalence of polycystic ovarian syndrome (PCOS) in young women and the side effects of existing medication regimens, this study was performed with aim to evaluate the antioxidants and clinical effects of oral Curcumin Nanomicell capsule with the approach to improve the women's quality of life. Methods: This cross-sectional interventional open label study was performed on 20 patients with PCOS in Tehran from April 2018 to September 2019. The subjects received 50 mg Nanomicell capsule for 90 days every other day. Quantitative indexes of oxidative stress (serum level of Malondialdehyde, Superoxide dismutase, and Catalase) were analyzed at baseline and after the end of intervention; the patients' quality of life was evaluated as monthly. Data were analyzed by SPSS software (version 24) and paired t-test and U Mann-Whitney test. P<0.05 was considered statistically significant. Results: Continuous 3-month oral intake of Curcumin Nanomicell reduced the menstrual pain scores (p=0.003), anxiety and depression levels (p=0.007) and hirsutism (p<0.0001), but no significant relationship was observed between the use of 80 mg Curcumin Nanomicell as monthly and every other day and reduced serum level of oxidative stress factors and other factors related to the patients' quality of life (p>0.05). Conclusion: Curcumin Nanomicell improved some clinical signs of PCOs but antioxidant effect was not observed according to the serum biomarkers. However this pilot study on a small sample size opened up a new insight for future therapy of PCOs patients, further research in larger groups in longer time periods seems necessary.